WACANA ASIMILASI DALAM FILM TELEVISI "JANGAN PANGGIL AKU CINA" - Rinasari Kusuma, Dewi Kartika Sari (IKOM UMY, 2015)
Television film entitled "Jangan Panggil Aku Cina" is o television movie Ioaded with meaning of assimilation. By using the method of Van Dijk model of discourse analysis, film "Jangan Panggil Aku Cina" has two levels of analysis: micro and macro onalysis. lvlicro analysis related to the meaning of the message in the film while the mocro-analysis analyze in a social context, cultural and political issues in lndonesia